Evaluation of Information in Summaries of Product Characteristics (SmPCs) on the Use of a Medicine in Patients With Hepatic Impairment - Weersink, Rianne A.; Timmermans, Lotte; Monster-Simons, Margje H.; Mol, Peter G. M.; Metselaar, Herold J.; Borgsteede, Sander D.; Taxis, Katja (Frontiers in Pharmacology, 2019)
Background: In 2005, the European Medicines Agency (EMA) released guidance on pharmacokinetic studies in patients with hepatic impairment. This guidance describes the design of these studies and what information should be presented in the Summary of Product Characteristics (SmPC). We aim to evaluate the availability and clinical applicability of information on medicine use in patients with hepatic impairment in SmPCs and registrational dossiers of recently approved medicines. Methods: We reviewed SmPC information on use in patients with hepatic impairment of 51 new medicines authorized between 2015 and 2017. Per medicine, we assessed the availability of nine information items derived from the EMA guidance; i.e., type of hepatic disease studied, stratification by severity of hepatic impairment, influence of hepatic impairment on the pharmacokinetics, safety advice in mild, moderate and severe hepatic impairment and dosing recommendation in mild, moderate and severe hepatic impairment. If unavailable, the European Public Assessment Report (EPAR) and study report were consulted consecutively. Of available items, clinical applicability was assessed by labelling information as “clear” or “ambiguous”. Results: Of 51 medicines, 15 had no pharmacokinetic study in patients with hepatic impairment described in their SmPC. The other 36 SmPCs contained on average 7 of the 9 information items (range 4-9). One SmPC contained all 9 items and after consulting the study reports 11 SmPCs were complete. The item “type of hepatic disease studied” was available in one SmPC, though could be retrieved in 21 study reports. Regarding clinical applicability, there was no medicine with all information items available and clearly formulated in the SmPC. A total of 12 medicines (33%) contained only clearly formulated information, while 24 (67%) contained at least one ambiguously formulated information item (range 0-4). Items often ambiguously formulated were: “definition of mild, moderate and severe hepatic impairment” (15 ambiguous SmPCs) and “safety advice in severe hepatic impairment” (17 ambiguous SmPCs). Conclusion: While SmPCs contain a large part of information requested by the EMA, clinical applicability seems low as it is often unclear to which specific type of hepatic disease patient the advice applies. This can negatively influence the practical use by healthcare professionals.